2007
DOI: 10.1088/0031-9155/52/13/021
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of tantalum markers used in the treatment of uveal melanoma with proton beam therapy

Abstract: Metallic fiducial markers are frequently implanted in patients prior to external-beam radiation therapy to facilitate tumor localization. There is little information in the literature, however, about the perturbations in proton absorbed-dose distribution these objects cause. The aim of this study was to assess the dosimetric impact of perturbations caused by 2.5 mm diameter by 0.2 mm thick tantalum fiducial markers when used in proton therapy for treating uveal melanoma. Absorbed dose perturbations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 46 publications
4
65
0
Order By: Relevance
“…In a proof-of-concept analysis, Newhauser et al (2005) found that accuracy could be improved by using a Monte Carlo simulation model. More recently, this model was used to study the relative dose perturbations caused by small implanted fiducial markers in the eye (Newhauser et al 2007b) Another limitation of presently available treatment planning systems is that they do not predict the dose per monitor unit (D/MU) value. Accurate D/MU predictions to within 3% were reported by Kooy et al (2003) using an analytical algorithm developed for proton fields with a wide cross-sectional area and deep penetration range.…”
Section: Introductionmentioning
confidence: 99%
“…In a proof-of-concept analysis, Newhauser et al (2005) found that accuracy could be improved by using a Monte Carlo simulation model. More recently, this model was used to study the relative dose perturbations caused by small implanted fiducial markers in the eye (Newhauser et al 2007b) Another limitation of presently available treatment planning systems is that they do not predict the dose per monitor unit (D/MU) value. Accurate D/MU predictions to within 3% were reported by Kooy et al (2003) using an analytical algorithm developed for proton fields with a wide cross-sectional area and deep penetration range.…”
Section: Introductionmentioning
confidence: 99%
“…Previous fiducials used in radiotherapy include steel beads, titanium cylinders, tantalum disks and gold beads [1,11,13,15]. These implants are not widely available and were used exclusively in the reporting centers.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, various fiducial systems are frequently utilized to deliver daily image-guided stereotactic proton therapy. These include a rigid head frame attached to the skull, steel beads implanted into the outer table of the skull, tantalum markers attached to the sclera for ocular tumors, and stainless steel markers implanted into the prostate for prostate cancer [1,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Newhauser et al indicated that implanted tantalum clips may, in certain circumstances, cause dose shadows that could lower the tumor dose and theoretically compromise local tumor control. 15 To overcome these disadvantages, several noninvasive tumorreferencing approaches have been proposed. Most of them rely on a 2D (two-dimensional) approach for the localization of the 2D eye position on the image captured by a single video camera.…”
Section: Introductionmentioning
confidence: 99%